University library and the new challenges of the XXI century. - Marta Liduvina Medina del Sol; Ana Aurora Home Martínez; Adriana María Solsona Medina; Dayanay Collado Almeida; Elías Jesús Solsona Medina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
University libraries face the new challenges and kind of work of this century and turn into centres for the research and learning. This bibliographic review is focused on the changes that have marked the transition to the new paradigm of scientific-informative activity, with the arrival of information and communication technologies and the transformation of higher education which have an impact on other kinds of teaching and learning process in the information and knowledge society of the XXI century. We discuss the necessity of developing skills and knowledge among the librarians as part of a process of informational alphabetization. Some styles of work in these institutions are described, which help strengthen the information and knowledge management and the learning process. The main objective is to inform about the work the university library and its transformation into a knowledge industry facing the challenges of this century.